2021
DOI: 10.1111/ppc.12730
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on the quality of life and depression, anxiety, and stress levels of individuals above the age of eighteen

Abstract: Purpose The aim of this study is to analyze the impact of the COVID‐19 pandemic on the quality of life and the depression, anxiety, and stress levels of individuals above the age of eighteen. Design and Methods This study used the snowball method. Data were collected using the sociodemographic question form, the Depression, Anxiety, Stress Scale‐21, and the SF‐12 Life Quality Scale. Findings A statistically significant relationship ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
(42 reference statements)
3
14
0
Order By: Relevance
“…Although publication on the impact of COVID-19 is in its nascent phases, emerging research both reaffirms the relationship between anxiety and QOL and highlights potential correlates, particularly among non-clinical populations. Supporting prior research, anxiety symptom severity was negatively correlated with QOL among individuals under COVID lockdown conditions, with females, older individuals, unemployed individuals, and individuals with or a caretaker for a chronic medical condition experiencing lower levels of QOL [87,88]. Research during COVID has also highlighted the role of maladaptive coping strategies, such that higher levels of avoidant coping, substance use, and denial as methods to cope with COVID-related anxiety predicted poorer QOL for non-clinical adults [89,90].…”
Section: Qol and Anxiety During Covid-19supporting
confidence: 55%
“…Although publication on the impact of COVID-19 is in its nascent phases, emerging research both reaffirms the relationship between anxiety and QOL and highlights potential correlates, particularly among non-clinical populations. Supporting prior research, anxiety symptom severity was negatively correlated with QOL among individuals under COVID lockdown conditions, with females, older individuals, unemployed individuals, and individuals with or a caretaker for a chronic medical condition experiencing lower levels of QOL [87,88]. Research during COVID has also highlighted the role of maladaptive coping strategies, such that higher levels of avoidant coping, substance use, and denial as methods to cope with COVID-related anxiety predicted poorer QOL for non-clinical adults [89,90].…”
Section: Qol and Anxiety During Covid-19supporting
confidence: 55%
“…Furthermore, an Italian study showed that physical activity in patients with NMD, was significantly reduced during lockdown [ 17 ] which may have negative health consequences as physical activity and exercises are recommended to reduce progression of muscle weakness [ 18 ]. There are also indications of negative emotional consequences of the pandemic and the associated restrictions from studies of the general public [ 19 ] and a few studies in patients with NMD, primarily ALS, such as concerns about COVID-19 infection, loneliness, anxiety and depression [ 12 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cronbach alpha internal consistency coefficient for the whole scale was computed as α=0.82. Recommended cut-off scores for the DASS-21 were used to categorize the participants as follows: depression was categorized as normal (0-9), mild (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and severe (≥21); anxiety was categorized as normal (0-7), mild (8)(9)(10)(11)(12)(13)(14), and severe (≥15), and stress was categorized as normal (0-14), mild (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and severe (≥26).…”
Section: Depression Anxiety Stress Scale (Dass-21)mentioning
confidence: 99%
“…(10,12,14) Several studies have confirmed that mental health issues have rapidly increased after the outbreak of the pandemic. (2,9,(15)(16) A recent study conducted in Italy reported that anxiety, depression, stress, and other mental health diseases increased particularly during the first wave of lockdown. (13) Many reports have confirmed that the COVID-19 pandemic is associated with higher distress, anxiety, anger, stress, and agitation in the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation